1998
DOI: 10.1093/carcin/19.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CYP1A1 and CYP1B1 in human breast epithelial cells and breast tumor cells

Abstract: Human cytochromes P450 1A1 (CYP1A1) and P450 1B1 (CYP1B1) catalyze the metabolic activation of a number of procarcinogens and the hydroxylation of 17beta-estradiol (E2) at the C-2 and C-4 positions, respectively. The aromatic hydrocarbon receptor (AhR) agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) has a marked effect on estrogen metabolism in MCF-7 breast-tumor cells by induction of these two enzymes. To investigate whether induction of CYP1A1 and CYP1B1 by AhR agonists and the associated increase in E2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
175
1
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(198 citation statements)
references
References 38 publications
19
175
1
2
Order By: Relevance
“…In liver, TCDD increases the levels of CYP1A1 and CYP1A2 relative to CYP1B1 (Walker et al, 1999), hence 2-hydroxylation predominates over 4-hydroxylation. Similar results have been reported in several breast epithelial tumor and nontumor cell lines where TCDD strongly induced CYP1A1 activity with resultant 2-hydroxyestradiol formation as the major E 2 metabolite (Spink et al, 1998). In this regard, increased production of 2-hydroxyestradiol relative to 4-hydroxyestradiol and 16α-hydroxyestrone has been observed after exposure to indole 3-carbinol, a dietary micronutrient and AHR proligand.…”
Section: Effects Of Gender and Sex Hormones In The Tcdd Dose-responsesupporting
confidence: 86%
“…In liver, TCDD increases the levels of CYP1A1 and CYP1A2 relative to CYP1B1 (Walker et al, 1999), hence 2-hydroxylation predominates over 4-hydroxylation. Similar results have been reported in several breast epithelial tumor and nontumor cell lines where TCDD strongly induced CYP1A1 activity with resultant 2-hydroxyestradiol formation as the major E 2 metabolite (Spink et al, 1998). In this regard, increased production of 2-hydroxyestradiol relative to 4-hydroxyestradiol and 16α-hydroxyestrone has been observed after exposure to indole 3-carbinol, a dietary micronutrient and AHR proligand.…”
Section: Effects Of Gender and Sex Hormones In The Tcdd Dose-responsesupporting
confidence: 86%
“…Another important factor is excessive formation of 4-OHE 1 (E 2 ) as a major metabolite of E 1 (E 2 ), catalyzed by CYP1B1 [30][31][32]. Minimization of estrogen-DNA adduct formation occurs when COMT is present at high levels because methoxylation of 4-OHE 1 (E 2 ) is one of the key elements in reducing adduct formation.…”
Section: Resultsmentioning
confidence: 99%
“…In extrahepatic tissues, cytochrome P450 (CYP)1A1 and CYP1B1 predominantly metabolize the natural estrogens E 1 and E 2 to 2-and 4-catechol estrogens (CE), respectively [30][31][32], which can be competitively oxidized to their respective semiquinones and quinones. In general, the CE are inactivated by conjugating reactions, such as glucuronidation and sulfation.…”
Section: Introductionmentioning
confidence: 99%
“…CYP1B1 mRNA detection does not always correlate with CYP1B1 protein expression (67). RNA-PCR studies have shown that expression of CYP1B1 is equivalent in normal and tumor tissues, whereas immunohistochemical analysis and activity assays indicate that protein expression is increased in tumors (4,5,63,68).…”
Section: Problems With Mrna Detectionmentioning
confidence: 99%